A concept for evaluating innovation related actions under the EU Structural Funds - Tanja Fleischhauer (European Regional Science Association (ERSA), 2005)
Beginning with 1 January 2007 a new programming period of the European Structural Funds is going to start (2007-2013). The negotiations about the contents and the re-gional structure of the funds are still in progress, but the European Commission has al-ready published her thoughts in the Third Cohesion Report and in some draft regulations (KOM 2004/492; KOM 2004/493; KOM 2004/494; KOM 2004/495). Main elements of the Commission's proposal are the concentration of funding for the least developed regions and Member States, the thematic concentration on the strategies of Lisbon and Gothenburg as well as institutional capacity building (KOM 2004: XXXVI). The Commission is willing to introduce a new priority ('Regional Competitiveness and Employment') as a successor of Objective 2 to strengthen the regional competitiveness and the employment. The new priority is following the Lisbon Strategy and therefore mainly promoting innovation and the knowledge society (ERDMENGER; ZIEGLER 2004: 327). Besides the textual change of the funding the Commission's proposal is making clear, that the evaluation of structural funding is – as it has been in the past programming pe-riods – a necessary condition to achieve the quality standards of funding. This means that ex-ante-, mid-term- as well as ex-post-Evaluations remain obligatory (KOM 2004: XXXVII). At present a complete and consistent evaluation of the funding-effects can not necessar-ily take place, because of a lack of statistical information on the regional level as well as difficulties in comparing the regions' funding achievements (z.B. TOEPEL 2000: 400; BEYWL; TAUT 2000: 359). These problems are especially true for the evaluation of innova-tion related actions, because the general problems are accumulated with problems of the measurability of innovation (PERRIN 2000: 5ff; DIEZ 2001: 912ff; AUTIO 1998: 132). If the plans of the commission happen to turn into law on 1 January 2007, the importance of Innovation related actions will increase as well as the political requirement to measure and value their effects. The goal of this paper is to contribute to an alternative concept to evaluate innovation related actions under the EU Structural Funds. Main differences between the present evaluation concept and the paper's proposal point to problems, which were identified by two case studies of existing evaluations of innovation related actions.
Keywords: 330